THE ROLE OF ESG AWARENESS AND MAQASHID SYARIAH ORIENTATION IN SHAPING GREEN INVESTMENT INTENTION AND BEHAVIOR, MODERATED BY GREEN ATTITUDE - Muh.Fiqran; Nurhasnita; Ahyar Aswardi Ibra; Andi Putri Sadrianti (International Journal of Multidisciplinary Reseach, 2025)
This article discusses how the growing awareness of global sustainability has encouraged the integration of religious values and environmental principles into modern investment practices. This study aims to empirically examine the influence of ESG awareness and Maqashid Syariah orientation on green investment intention and green investment behavior, as well as the moderating role of green attitude between the two, in order to establish a scientific basis for the development of ethical, sustainable, and spiritually valuable green investment. This study uses an explanatory quantitative approach that aims to empirically test the influence of Environmental, Social, and Governance (ESG) awareness and Maqāṣid Syariah orientation on green investment intention and green investment behavior, with green attitude as a moderating variable and green investment intention as a mediating variable. The results show that ESG Awareness has a positive and significant effect on Investment Behavior, while Green Attitude has a negative effect on Green Investment. Meanwhile, Maqashid Syariah orientation does not show a significant effect on either of the two dependent variables. These findings indicate that rational understanding and awareness of sustainability values have a stronger impact on investment behavior than affective dimensions such as green attitude. In addition, these results show an attitude–behavior gap, where positive attitudes toward the environment are not fully realized in concrete actions.